Over‐the‐Counter Option Market Dividend Protection and “Biases” in the Black‐Scholes Model: A Note - GESKE, ROBERT; ROLL, RICHARD; SHASTRI, KULDEEP (Journal of Finance, 1983)
ABSTRACT Most options are traded over‐the‐counter (OTC) and are dividend “protected;” the exercise price decreases on the ex date by an amount equal to the dividend. This protection completely inhibits the early exercise of American call options. Nevertheless, OTC‐protected options have market values which differ systematically from Black‐Scholes values for European options on non‐dividend paying stocks. The pricing difference is related to both the variance of the underlying stock return and to time until expiration of the option, but it is quite small in dollar amount.